Can Online Short Courses Foster Business Education for Sustainable Development? - Dhakal, Subas (International Review of Research in Open and Distributed Learning, 2023)
The COVID-19 pandemic challenged the practice of traditional higher education providers (HEPs) and highlighted the need for innovative approaches to education for sustainable development. This research note focuses on online short courses (OSCs)—micro-credentials geared at upskilling or reskilling learners with a competitive application process and cost. It conducts (a) a rapid bibliometric analysis of literature on the nexus between OSCs and sustainable development and (b) an environmental scan of OSCs offered in Australia with a lens of sustainable development. An exploratory approach was adopted to analyze publicly available secondary data on scholarly literature and the courses offered. Findings reveal two key trends: (i) the nascent nature of literature on OSCs and sustainable development globally and (ii) the limited availability of sustainable development related OSCs in Australia. This research note makes broad analytical contributions to posit OSCs as an e-learning innovation to advance business education for sustainable development.